STRUGGLES OF LIVING MARTYRS IN PANDEMIC- IMPACT OF COVID-19 AMONG HEALTH WORKERS (International Journal of Food and Nutritional Sciences, 2022)
Pandemic shattered the life of everyone regardless of ethnicity, color, creed or religion. It caused complete breakdown of the existing systems around the world impacting every aspect of life. COVID-19 brought a sudden onset of contagious disease that affects health, disrupts services and businesses, and brings economic and social costs. Healthcare workers are working relentlessly despite the high risks of getting infected by SARS-Cov-2. Yet, the public’s appreciation stays on the surface level, through social media, whereas health workers all over the world get discriminated against in their daily lives. Many of the social and psychological challenges that are faced by health workers are often overlooked, and remain unaddressed. Apart from the constant fear of becoming a carrier of COVID-19, health workers are pushed to the brink with reduction in salaries and late payments. Hence the lives of these health workers were badly affected by stigma and trauma of COVID-19. The researchers initiated this quantitative study to understand the impact of COVID-19 among healthcare workers in Idukki and Ernakulam districts of Kerala state. The respondents (n=103) were selected for the study under purposive sampling. Data collection was done by questionnaire (Google Form). The result of the study reveals that COVID-19 has a significant impact in experiencing severe depression, stress, burnout, social stigma, low self-esteem and low job satisfaction among health workers.